A novel approach in the management of hyperhomocysteinemia. (August 2019) - Qureshi, Shaiba Sana; Gupta, Jeetendra Kumar; Goyal, Ahsas; Narayan Yadav, Harlokesh
Abstract: Hyperhomocysteinemia (Hhcy) is a biochemical alteration with plasma levels of homocysteine higher than 15 µmol/L, associated with atherosclerosis, and with vascular thrombosis by disrupting endothelial cells. Homocysteine is a sulfur-containing amino acid derived from methionine which is an essential amino acid. Excess homocysteine produced in the body is expelled out by liver and kidney from the systemic circulation. Hhcy is caused by the excess deficiencies of the vitamins like pyridoxine (B6), folic acid (B9), or cyanocobalamin (B12). High protein consumers are usually at risk for hyperhomocysteinemia because of low plasma B12 levels. It is approximated that mild Hhcy occurs in 5–7% of the general population and 40% in patients with vascular disease. Patients with heart failure, impaired renal function, and diabetes should be screened since the prevalence of Hhcy in these patients appears to be quite high. In this article, we hypothesise that citicoline is a novel drug for the management of Hhcy. Furthermore, the side effects of citicoline are also minimal and self-limiting. If this strategy is validated, citicoline will be the cost-effective way to be administered for Hhcy. Many evidences are available which suggest that ignoring homocysteine levels in patients with the vascular disease would be unwise. Thus, there is an urgent need for health care providers to develop effective preventions and interventions program (folic acid, Vitamin B6 and Vitamin B12 supplementation as well as lifestyle change) to reduce this disorder.